2020
DOI: 10.1111/1756-185x.13921
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of 14‐3‐3 η protein in rheumatoid arthritis: A meta‐analysis

Abstract: Rheumatoid arthritis (RA) is a chronic, inflammatory joint disease of autoimmune nature, characterized by painful, swollen joints that can severely impair physical function and quality of life. 1,2 The disease affects women 2-3 times more often than men and occurs at any age. 3 The peak incidence is between ages 50-60 years. In Western countries, the prevalence of RA is in the range of 0.5%-1.0% in White individuals, while the prevalence ratios were 0.45, 0.69 and 1.02 for women of Hispanic, Asian or African-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(103 reference statements)
0
7
0
1
Order By: Relevance
“…As can be seen from the table, the sensitivity and specificity vary widely but are consistently good with a meta-analysis of all studies estimating that a pooled sensitivity was 73% (95% CI: 71, 75) and the pooled specificity was 88% (95% CI: 87, 90). [ 21 ] This provides evidence that it could be a very useful bio-marker for diagnosis. Another pooled meta-analysis [ 22 ] showed that a pooled sensitivity of 14-3-3 η as 0.63 (95% CI: 0.60–0.66) and the pooled specificity as 0.90 (95% CI: 0.88–0.91).…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen from the table, the sensitivity and specificity vary widely but are consistently good with a meta-analysis of all studies estimating that a pooled sensitivity was 73% (95% CI: 71, 75) and the pooled specificity was 88% (95% CI: 87, 90). [ 21 ] This provides evidence that it could be a very useful bio-marker for diagnosis. Another pooled meta-analysis [ 22 ] showed that a pooled sensitivity of 14-3-3 η as 0.63 (95% CI: 0.60–0.66) and the pooled specificity as 0.90 (95% CI: 0.88–0.91).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent study, a panel of 4 biomarkers distinguished established RA patients from healthy controls with an AUC of >0.97 (32). Another study showed the ability of the RA‐associated 14‐3‐3 η protein (33) to distinguish RA from healthy controls with an ROC AUC of >0.92 for RA according to the ACR 1987 classification criteria (34). However, when combined with anti‐CCP and RF, the 30% false‐positive rate (34) may limit the clinical utility.…”
Section: Discussionmentioning
confidence: 99%
“…But when we compared the expression of the LRFN4 in PCa samples with different TNM staging, we noticed that the LRFN4 was upregulated in the patients with more advanced staging. The YWHA family proteins have been discovered to bind to various proteins such as transmembrane receptors and transcription factors, participating in intracellular protein transport, cell proliferation, apoptosis and signal transduction, etc (Wang et al 2020). It has been reported that the YWHAZ protein can enhance androgen receptor transcriptional activity in PCa and promote the adhesion and migration of various extracellular matrix proteins (Goc et al 2012;Murata et al 2012).…”
Section: Lrfn Protein Interaction Network Constructionmentioning
confidence: 99%